CONFLICT BETWEEN THE INDIVIDUAL AND SOCIETY IN THE NOVEL «ANNA KARENINA» (Bulletin of Innovative Research, 2026)
This article examines the dilemma of the confrontation between the individual and society in Leo Tolstoy’s novel «Anna Karenina». It explores the discrepancy between the heroine’s innermost aspirations and the moral precepts of the upper crust of the second half of the nineteenth century. Close attention is paid to the development of Anna’s mental state, the methods of social oppression, and the author’s ideological understanding of the issue.